Bioinformatics Study on Curcuma mangga Diterpenoids as Potential Anticancer Agents for Breast Cancer - Putri Khaerani Cahyaningrum; Indra Yudhawan; Binar Pratama; Nur Amalia Choironi (LPPM Universitas Abdurrab, 2025)
Breast cancer, with its aggresive subtypes and resistance, is a major cause of cancer-related mortality among women. Advancements of breast cancer drug discovery is great and survival rate is better than in the past, but still advanced breast cancer remain difficult to treat, emphasizing the need for searching of alternative therapeutic agents with proven efficacy and safety. Curcuma mangga contains diterpenoid compounds that have demonstrated cytotoxic potential against breast cancer cells. This study aimed to elucidate the molecular mechanisms and pharmacokinetic properties of diterpenoids from the n-hexane extract of C. mangga against ER-positive breast cancer using a network pharmacology approach. Four diterpenoids—(E)-Labda-8(17),12-diene-15,16-dial, (E)-15,16-Dinorlabda-8(17),11-dien-13-one, m-camphorene, and p-camphorene—were evaluated. Breast cancer-related genes were retrieved from the NCBI database, while compound targets were predicted using SwissTargetPrediction and SEA Search Server. Nineteen overlapping genes were identified as Potential Therapeutic Target Genes (PTTGs) and further analyzed through protein–protein interaction, Gene Ontology, and KEGG pathway enrichment analyses. Key targets included EGFR, AKT1, CYP19A1, and PGR, which are involved in cell proliferation, survival, and hormone-regulated signaling pathways. ADME and toxicity predictions indicated favorable oral bioavailability for labdane diterpenoids, although potential hepatotoxicity and mutagenicity were observed in certain compounds. Overall, (E)-Labda-8(17),12-diene-15,16-dial emerged as the most promising candidate, supporting its further investigation as a potential therapeutic agent for ER-positive breast cancer.